2011
DOI: 10.1111/j.1468-5914.2011.00470.x
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Plurality and Context in Social Values

Abstract: The study of social values has its origins in the study of both cross cultural and within cultural differences in latent or manifest definitions of the right social order to achieve the good life. To this extent, the social scientific literature is replete with references to them. Yet, researchers either use the term values Social values are often used interchangeably with that of attitudes or treated as a post‐hoc explanatory concept. When values are the focal research point, such endeavours predominantly dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 52 publications
4
36
0
1
Order By: Relevance
“…More specifically to environment and Italy, Mannetti (2004) found that although self-identity can play an important role in good intentions to recycle etc., the perceived behavioural 7 control is always the second best contributor in their structural equations models. A more refined discussion of the relationship between values and behaviour is offered by Tsirogianni and Gaskell (2011) who refer to the distinction, originally proposed by Charles Morris (Morris, 1956) example, the availability of recycling facilities, the quality of public transport, the market supply of goods, or pricing regimes can strongly affect people's engagement in pro-environmental behaviour (Vining & Ebreo, 1992;Vlek & Stek, 2007).…”
Section: Insert Tablementioning
confidence: 99%
“…More specifically to environment and Italy, Mannetti (2004) found that although self-identity can play an important role in good intentions to recycle etc., the perceived behavioural 7 control is always the second best contributor in their structural equations models. A more refined discussion of the relationship between values and behaviour is offered by Tsirogianni and Gaskell (2011) who refer to the distinction, originally proposed by Charles Morris (Morris, 1956) example, the availability of recycling facilities, the quality of public transport, the market supply of goods, or pricing regimes can strongly affect people's engagement in pro-environmental behaviour (Vining & Ebreo, 1992;Vlek & Stek, 2007).…”
Section: Insert Tablementioning
confidence: 99%
“…The origin of personal values research dates back to the 1920s (Tsirogianni & Gaskell, 2011). In the early days of personal value research, the central theme of discussion was to identify the universal value types that exist among all people in all societies (Rohan, 2000).…”
Section: Key Studies In Personal Valuesmentioning
confidence: 99%
“…If two personal values are close to each other, they are more interrelated and share similar characteristics. On the other hand, when two personal values are separated (or on opposite sides of the structure), these values are in conflict with each other (Tsirogianni & Gaskell, 2011). For example, in the figure, achievement and power values are highly interrelated as they embrace the pursuit of individual interests; however, these values conflict with universalism and benevolence that serve collective interests.…”
Section: Schwartz Value Surveymentioning
confidence: 99%
See 2 more Smart Citations